Королевский сорняк: [роман] / Татьяна Гармаш-Роффе - Гармаш-Роффе Татьяна (Детектив высшей пробы, 2008)
Экземпляры: АБ (20180601) / Инвентарный номер: 49034 / Цена: 95.47 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 20 / ББК: 84(2Рос=Рус)6